Light-driven continuous rotating Möbius strip actuators - Zhen-Zhou Nie (Nature Portfolio, 2021)
Shape morphing materials are usually difficult to operate in a continuous fashion. Nie et al. fabricate stripes with liquid crystalline elastomers that can be given a Möbius-like morphology with seamless material composition, and perpetually driven under photothermally induced actuation.